STUDENTS’ ATTITUDE TOWARD E- LEARNING DURING COVID 19 PANDEMIC AT STKIP PGRI SUMATERA BARAT - Rani Autila (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Nasional, 2022)
This research investigated students’ attitude toward E- Learning during Covid 19 Pandemic at Sosiology Departement of STKIP PGRI Sumatera Barat. Attitude can influence students’ way of thinking, feeling, or making sense of the learning process. Thus, teachers need to know about students’ attitude. In this study, researcher investigated students’ attitude involve students’ thinking, feeling and behavior using empirical data. The purpose was to find how are the students’ attitude of thinking, feeling and behavior on the use of E-learning during Covid 19 Pandemic at Sosiology Departement of STKIP PGRI Sumatera Barat. The method of research is quantitative method with the design was descriptive or survey research. The type of survey was Cross-sectional research. This study examines all students at Sosiology Departement session 2020 A of STKIP PGRI Sumatera Barat which totally twentythree students. The data were taken form a questionnaire. The findings of the research showed that students have a positive thinking and feeling toward e- learning with mean average 3,5 (N=23, st.d= 0.9). In contrast, they have a negative behavior toward e- learning with mean average 2,9 (N=23, st.d =1,0). Thus, it is sugested for teacher to change their students from negative attitude into positive attitude.